Prevalence of Sarcocystis Species (Sarcocystis ovicanis and Sarcocystis capricanis) in Tongue Muscle of Sheep and Goats in Duhok Province, Kurdistan Region, North Iraq - Zangana, Ihsan K.; Hussein, Shivan N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Sarcocystis species are coccidian protozoan parasites of the phylum apicomplexa. The prevalence of Sarcocystis species (Sarcocystis ovicanis and Sarcocystis capricanis) in tongue muscle of sheep and goats that collected from abattoir and outside of abattoir (at Butchers Markets) in Duhok province was determined for the first time during the period of 4 months from September 01, 2014, to January 03, 2015. Three techniques were applied for this purpose. Direct scotch cellophane adhesive tape test, muscle mincing and squash method, and pepsin digestion technique. The overall prevalence was 97% in sheep and 100% in goats. No significant difference (p>0.05) was obtained between male and female of both species. Histopathological analysis revealed different size and shape of microcysts with thick cyst wall, in addition to mild histological changes.